Will to surviv3 - Walters, Eric, 1957- (Walters, Eric, 1957- Rule of 3., 2017)
Four months ago, when the blackout happened, Adam had to do something terrible, but necessary, to protect his family and his home. However, it changed him, and he knows he will never be the same. His neighborhood now made into a fortress, he and others do whatever they can to keep each other safe and protect their resources from vicious outside forces. Somebody seems on a mission to destroy their neighborhood, and has a personal vendetta against Adam--a situation which may force Adam to cross the last moral line he has.